DEVELOPING STUDENTâS COMMUNICATIVE COMPETENCE THROUGH ENGLISH LEARNING MATERIALS FOR THE THIRD GRADE OF PRIMARY SCHOOL STUDENT: A CASE STUDY - Tambunan, Jenny Flora (Universitas Esa Unggul, 2016)
AbstractThis study was conducted to reveal kinds of English learning materials used in the context of learning English as a foreign language to develop studentsâ communicative competence for the third grade of primary students. A single unit of learning materials stated in lesson plan and implemented in the teaching and learning process were the main sources in this study besides interview as the additional source. A case study was used as the design of this study. The result of three document analysis from lesson plan indicates that the learning materials used by the teacher are teacher language whether spoken or written, and any materials used that support the topic such as text book as the main source, songs and stories. The result of observation indicates that teacher talk and teacher language whether spoken or written through songs and stories can support the development of studentsâ basic communicative competence. Last, the result of interview emphasizes on any approaches used by the teacher by knowing studentâs interest and relates it with the learning materials used. In this case, this study indicates that the eight learning materials stated in three lesson plans and carried out in four classroom observations show that all of the learning material can develop studentsâ communicative competence through songs, stories, and any learning materials support the topics.Â Keywords: developing studentâs, english learning materials, primary school studentÂ AbstrakPenelitian ini bertujuan untuk menggambarkan jenis-jenis materi pembelajaran yang digunakan unutk mengembangkan kemampuan komunikasi siswa dalam konteks kelas. Unit materi pembelajaran yang direnakan dalam rangan pelaksanaan pembelajaran (RPP) dan diimplementasikan dalam proses belajar mengajar merupakan sumber data utama dalam penelitian ini selain wawancara sebagai sumber tambahannya. Studi kasus dipilih sebagai desain dari penelitian ini. Hasil analisis yang diperoleh dari tiga rencana pembelajaran yang direncanakan dan digunakan selama proses belajar mengajar adalah pembicaraan guru baik lisan maupun tulisan,Â dan segala bahan ajar yang mendukung materi pembelajaran tersebut seperu buku paket sebagi acuan utama, lagu dan cerita/dongeng adalah materi pembelajaran yang digunakan dan dapat mendukung kemampuan kemampuan dasar siswa. Melalui 1x wawancara hasil wawancara menekankan materi pembelajaran pada bahasa guru melalui pendekatan-pendekatan yang dilakukan guru dengan mengetahui minat dan kesenangan siswa yang nantinya dihubungkan dengan materi pembelajaran. Dalam hal ini penelitian ini menunjukkan bahawa delapam materi pembelajaran yang terdapat dalam tiga rencana pembelajaran yang diimplementasikan dalam empat proses belajar mengajar dapat mengembangkan kemampuan berkomunikasi anak melalui lagu, certa dan bebabgai materi pembelajaran lain yang mendukung.Â Kata Kunci: materi pembelajaran, bahasa inggris, siswa sekolah dasar